PROBLEM ANALYSIS IN ISLAMIC COOPERATIVE IMPLEMENTATION FOR KARANGASRI FARMER GROUP KAMPUNG DURIAN PONOROGO - Faaza Frisky Aulia; Atika Rukminastiti Masrifah (Universitas Darussalam Gontor, 2021)
Cooperatives in Indonesia is the cornerstone of the economy for all people, especially those with low economies. Agriculture in Indonesia experienced a decline in 2017. One of the problem factors is the problem of capital. To overcome the problem of capital in agriculture, the right step is the establishment of a cooperative. The cooperative will regulate the financial circulation of the farmer groups. The farmer group that is the object of this research is the Karang Asri Kamnpung Durian Ngebel farmer group. This Karang Asri farmer group is the focus of this research because it has the potential for agricultural products that are much sought after by the community, namely durian fruit. In this study, the researcher will analyze the problems that exist in the Karang Asri farmer groups in Durian Ngebel Village which are the causes for the not yet established cooperatives in the farmer groups and formulate a cooperative model that can be established in the Karang Asri farmer groups. The method used in this research is descriptive qualitative with data collection techniques through, observation, interviews, and documentation. By interviewing the head of the Karang Asri farmer group representing the entire group. The results of this study indicate that six problem sectors are ranging from human resources, natural resources, production, distribution, systems, and problems from outside the farmer group. The problems that exist are divided into two groups, namely roots and branches. The root problem is the main problem because there is no cooperative in the farmer group. The branch problem is a factor that indirectly causes the absence of a cooperative. Then the cooperative model that was successfully designed was the sharia producer cooperative. It is hoped that this cooperative model will be a capital solution and also all problems that exist in farmer groups.